Anteseden Nilai Utilitarian Dan Minat Loyalitas Nasabah Bank Syariah - Fariz, Irfan Nur; Widiyanto, Ibnu (Diponegoro Journal of Management, 2014)
This research was conducted at the Semarang Branch of Bank Syariah Mandiri. Based on data of total costumer savings showed that reduction in 2012-2013 though the costumer increased every year. This research aims obtain empirical evidence effects of Financial Bond, Social Bond, and Structural Bond to Utilitarian Value impact on Loyalty Interest.The sample of this research is the customers of Semarang Branch of Bank Syariah Mandiri amounted to 100 people. This research used quantitative analysis method with multiple linear regression.The result of this research showed that Financial Bond (0,444), Social Bond (0,263), and Structural Bond (0,244) have positive effect on Utilitarian Value. While Financial Bond (0,294), Sosial Bond (0,227), Structural Bond (0,176), and Utilitarian Value (0,394) have positive effect on Loyality Intention.